Tinjauan Yuridis Pengawasan Keuangan Desa Berdasarkan Undang-Undang No. 6 Tahun 2014 Tentang Desa Dihubungkan dengan Pertanggungjawaban Kepala Desa - Panjaitan, Debora Agatha Christie; Hasan, Ida Roharti; Hamimah, Siti (Universitas Pahlawan Tuanku Tambusai, 2024)
Village government currently has its own autonomy with the emergence of a new legal product, namely Law Number 6 of 2014 which gives village-scale local authority to regulate and manage the interests of village communities effectively and efficiently, which is implemented by the village. This research aims to determine the function of financial management village as well as the supervisory function of the implementation of village government as a form of responsibility of the village head based on UU No.6 Tahun 2014 concerning Villages. This research uses normative juridical research with a research focus based on the legal basis used in research and procedures for its implementation in village communities. The research approach used is a statutory approach regarding the proposed study material and a conceptual approach. The primary data used comes from UU No.6 Tahun 2014, and several written regulations. Apart from that, secondary data comes from library materials by collecting field facts in the form of interviews and written materials contained in articles, books, scientific works which provide explanations of laws and regulations related to the problems to be studied. As well as additional material through dictionaries and encyclopedias. The data collection technique used is documentation/library study. The data collection technique used is documentation/library study. Transparency and compliance with laws and regulations are the keys to building a healthy relationship between financial supervision and village head accountability.